Mirror cognitions and behaviours in people concerned about their body shape - Farrell, C; Shafran, R; Fairburn, C (2004)
The present study aimed to test the hypothesis that women with high shape concern would differ in their use of mirrors from women with low levels of shape concern. The "Mirror Questionnaire" was completed by 150 women, half of whom had high levels of shape concern. The findings support the notion that women with high shape concern differ from those with low concern in their use of mirrors, and argue for further investigation of the role of mirror cognitions and behaviours in the maintenance of body image disturbance.